2018
DOI: 10.5826/dpc.0801a15
|View full text |Cite
|
Sign up to set email alerts
|

The role of reflectance confocal microscopy in a case of Bowen’s disease difficult to diagnose

Abstract: There have been limited reports describing reflectance confocal microscopy (RCM) features of Bowen’s disease (BD). Herein, we describe the RCM features of a pigmented BD with atypical dermoscopic features, mimicking a melanoma. This case highlights the importance of RCM in a challenging BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…These are: presence of atypical honeycomb pattern, atypical keratinocytes of different sizes and shapes, and "button-hole signs" consistent with tortuous blood vessels. A potential diagnostic point of discussion is the presence of numerous bright, large, round or dendritic cells infiltrating the epidermis, as previously observed [7,9]. Recently, three challenging cases of pigmented Bowen's disease were reported and wrongly diagnosed as melanoma due to the high density of dendritic cells observed using RCM [8].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These are: presence of atypical honeycomb pattern, atypical keratinocytes of different sizes and shapes, and "button-hole signs" consistent with tortuous blood vessels. A potential diagnostic point of discussion is the presence of numerous bright, large, round or dendritic cells infiltrating the epidermis, as previously observed [7,9]. Recently, three challenging cases of pigmented Bowen's disease were reported and wrongly diagnosed as melanoma due to the high density of dendritic cells observed using RCM [8].…”
Section: Discussionmentioning
confidence: 82%
“…Reflectance confocal microscopy (RCM) is a noninvasive technique mostly used for differential diagnosis of pigmented, melanocytic and nonmelanocytic skin lesions. To date, few data are available regarding its use in the diagnosis of pBD [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to visualize DEJ in detail and follicular structures for signs of dendritic cell infiltration to rule out LM. Other clues for pBD are numerous marked small bright rings at DEJ [ 5 , 6 ]. Since DEJ is infiltrated by malignant melanocytes in LM, presence of regularly shaped bright rims can signify pigmented AK/pBD.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported the RCM features of non-genital pigmented Bowen’s disease and their histopathological correlations. 2 , 7 , 8 , 9 They mainly consist of parakeratosis, irregular honeycomb pattern (indicative of keratinocyte atypia and pleomorphism), edged papillae (due to hyperpigmentation of keratinocytes of the basal layer), and coiled vessels in the dermal papillae. Other observed findings are represented by round nucleated cells often with a targetoid appearance throughout the epidermis (corresponding to dyskeratotic keratinocytes), intraepidermal hyperreflective dendritic, spindle-shaped cells (corresponding to Langerhans cells at immunostaining), and plump bright cells in the papillary dermis (corresponding to melanophages).…”
Section: Discussionmentioning
confidence: 99%
“…Other observed findings are represented by round nucleated cells often with a targetoid appearance throughout the epidermis (corresponding to dyskeratotic keratinocytes), intraepidermal hyperreflective dendritic, spindle-shaped cells (corresponding to Langerhans cells at immunostaining), and plump bright cells in the papillary dermis (corresponding to melanophages). 2 , 7 , 8 , 9 It must be highlighted that the dendritic cells may represent a confounder finding as they may also correspond to atypical melanocytes and could lead to the wrong diagnosis of melanoma, 9 and that the differential diagnosis of melanophages with pigmented cells of Bowen’s disease may not be easy due to the epidermis disruption and tumor cell heavy pigmentation.…”
Section: Discussionmentioning
confidence: 99%